Are there any potential drug-drug interactions with oral inhaler medications?: A retrospective study - TEZCAN, SONGÜL (My University, 2024)
Background: Oral inhaler medications (OIMs) are widely used for many respiratory diseases. Although OIMs have minimal systemic effects, they may cause potential drug-drug interactions (pDDIs). Objectives: This study aims to evaluate drug interactions in patients using OIMs. Methods: This retrospective, and descriptive study was conducted in a community pharmacy in Istanbul (Turkey) between January 1, andMay 312,021. Prescriptions of all asthma and COPD patients aged 18 and over on the specified date were included in the study. Data were collected from the pharmacy information system. Sociodemograhic characteristics were recorded. pDDIs were analyzed via Medscape and Lexicomp drug interaction checker databases. Significant (monitor closely), Serious (use alternative), Contraindicated categories in the Medscape database and D (consider treatment modification) and X (avoid combination) categories in the Lexi- Interact™ database were evaluated as pDDIs. SPSS analysis was performed. Results: A total of 54 asthma and 42 chronic obstructive pulmonary disease (COPD) patients were included in the study. Most asthma (76%) and COPD (83%) patients were found to have at least one comorbid disease. A total of81 pDDIs were identified in the Medscape database in asthma patients, and 86.5% of them were classified as “monitor closely”. A total of 12 drug interactions were detected in the Lexicomp database, with 75% of them were “D” category for asthma patients. In the prescriptions of COPD patients, a total of 162 drug interactions were determined via the Medscape database, with 94.4% classified as “monitor closely”. A total of 13 drug interactions were detected in the Lexicomp database, with 61.5% of them falling into the “X” category for COPD patients. Conclusions: According to the results of this study COPD patients who may be at a high risk of experiencing pDDIs. Healthcare providers should consider the individual patient’s clinical profile, including comorbidities and medication regimen, to minimize the risk of pDDIs and optimize treatment outcomes. Further research is needed to elucidate the mechanisms underlying these findings and develop tailored strategies to diminish the risks associated with pDDIs in respiratory disease management.
Keywords: Asthma; Chronic obstructive pulmonary disease; Potential drug-drug interactions; Oral inhaler medications